PERAN BRAND LOVE MEMEDIASI PENGARUH SOCIAL MEDIA MARKETING TERHADAP BRAND LOYALTY PADA UMKM KULINER DI DENPASAR - Ida Ayu Putri Widiasuari Riyasa; Nyoman Indah Kusuma Dewi; Ni Putu Maha Lina (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2023)
Social media is currently growing quite rapidly with the development of technology and information in the industrial era 4.0. In line with the use of the internet which is growing quite rapidly, it can be used by Micro, Small and Medium Enterprises to market their products online. The purpose of this study is to explain the role of brand love in mediating the influence of social media marketing on brand loyalty in culinary SMEs in Denpasar. 110 respondents were used in the research by taking purposive sampling technique. The data analysis used is a Path Analysis technique with complete Sobel testing to examine the role of mediation. The results showed that 1) social media marketing had a positive and significant effect on brand loyalty to Culinary MSME consumers in Denpasar, 2) social media marketing had a positive and significant effect on brand love among Culinary MSME consumers in Denpasar, 3) brand love had a positive and significant effect on brand loyalty to Culinary MSME consumers in Denpasar, 4) brand love is able to mediate the influence of social media marketing on brand loyalty to Culinary MSME consumers in Denpasar. The implications of the research results are to continue to promote and be active on social media by providing good service and quality as well as promotions or discounts so that positive comments arise from consumers.